Determination of indicators for tests of polysept (polyhexamethylene guanidine hydrochloride) for flocculation properties - M. N. Guseva; M. I. Doronin; M. A. Shevchenko; D. V. Mikhalishin; Y. M. Gochmuradov; V. V. Mikhalishin; Y. S. El’kina (Ветеринария сегодня)
In vaccine production, it is particularly important to purify the virus-containing suspension in order to remove ballast proteins and fats, which, when present in high concentrations, are responsible for depression or allergic reactions in animals. Polyguanidine and its derivatives have long been used for such purposes. At present, the market offers polyhexamethylene guanidine hydrochloride, a cationic polyelectrolyte with aunique combination ofphysico-chemical and biocidal properties allowing for it to be used in nearly all spheres of economy. Flocculation properties of polysept (polyhexamethylene guanidine hydrochloride) vary from batch to batch, and this has necessitated the development of a test system for determination of the incoming material quality, which has a significant impacton virus antigen concentration during vaccine production. Seven batches of polyhexamethylene guanidine were tested for flocculation properties, changes in FMDV immunogenic component concentration in the virus-containing suspension, osmolality of solutions at different percentage concentrations. Indicators of incoming material suitability for FMD vaccine production were determined. The batches of polysept should be tested for flocculation properties at different concentrations of thepolymer (0.007, 0.0105 and 0.01575%) in dynamics during 24 hours. After this period, the turbidity of solutions should not exceed 30 FNU (formazin turbidity) at concentrations of 0.0105 and 0.01575%. It is also necessary to determine the osmolality of polysept solutions at different percentage concentrations (6, 8, 10, 12, 14%). Osmolality values should be within the following ranges: 260 ± 20 mOsm fora 6% solution; 330 ± 25 mOsm foran 8% solution; 400 ± 25 mOsm fora 10% solution; 460 ± 30 mOsm fora 12% solution; 520 ± 20 mOsm fora 14% solution.